Answered

Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

−3x + 7y = −16
−9x + 5y = 16

slove this


Sagot :

eu99li


{-3x+7y=-16 ⇒ -3x=-16-7y    (↓)

{-9x+5y=16

The second equation:

-9x+5y=16

3*(-3x)+5y=16         Substitute -3x    (↑)

3* (-16-7y)+5y=16

-48-21y+5y=16      /+48

-16y=64      /:(-16)

y=-4

-3x=-16-7y

-3x=-16-7*(-4)=-16+28=12

-3x=12    /:(-3)

x=-4

Solution: (-4; -4)